Evidence for the co-existence of distorted tetrahedral and trigonal bipyramidal aluminium sites in SrAl12O19 from Al-27 NMR studies - Harindranath, K.; Viswanath, K. Anusree; Chandran, C. Vinod; Braeuniger, Thomas; Madhu, Perunthiruthy K.; Ajithkumar, Thalasseril G.; Joy, Pattayil Alias (Solid State Communications, 2010)
Strontium aluminate, SrAl12O19, is a ceramic material having the hexagonal magnetoplumbite-type structure, with multiple Al coordination environments. An earlier low-field Al-27 solid-state NMR study reported five different Al sites in this system: one AlO4, one AlO5, and three AlO6 sites; whereas a later high-field study showed that the AlO5 site is a distorted AlO4 site with a very large quadrupolar coupling constant (similar to 20 MHz). Our magic angle spinning (MAS) and 3-quantum magic angle spinning (3QMAS) NMR studies at 7.05 T unambiguously show evidence for an AlO5 site. However, evidence for the presence of a distorted AlO4 site is obtained from studies at high fields (16.4 and 17.6 T), in addition to the AlO5 site. Thus the present solid-state NMR studies give evidence for the simultaneous presence of both the five-coordinated and distorted four-coordinated sites in this system. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Local structure; MQMAS; Nuclear magnetic resonance; Strontium aluminate